Recent scientific findings on the professional formation of technology teacher - Ihor Hevko (Kazimierz Wielki University, 2016)
The article reviews the latest scientific findings on the professional formation of technology teacher. It analyzes major approaches towards the models of major proficiency levelsand defines the notion of "professional identity of technology teacher".